(untitled) (Jurnal Pertanian Terpadu, 2025)
Efforts to develop livestock in East Kalimantan can be carried out by utilizing post-coal mining land. However, the low level of soil fertility and the limited availability of topsoil as a cover soil on post-mining land are constraints that must be considered. Efforts that can be made include planting mycorrhizal cover crops and applying local microorganism-based organic fertilizers (MOL). The experiment was conducted by planting mycorrhizal legume seeds (Siratro) on topsoil and overburden soil placed in 10 kg polybags. Each type of soil was supplemented with local microorganisms (MOL) at concentrations of 0 mL, 10 mL, 20 mL, and 30 mL per litre of water. The experimental results showed that soil type influenced plant height, but both soil type and MOL concentration influenced the fresh weight and dry weight of Siratro plant crowns, as well as VAM root colonization, where higher MOL concentrations reduced Siratro crown production. Root colonization by VAM with increasing MOL concentration in topsoil showed a negative effect, where higher MOL concentrations resulted in lower VAM colonization on plant roots. Conversely, in overburden soil, increasing MOL concentration could increase VAM colonization.